Analysis of Organizational Behavior in Project Management Consultants Central Sulawesi Rehabilitation and Reconstruction Project (PMC CSRRP) - Malikus Djunaidi; Helmi Buyung Aulia Safrizal; RM Mochammad Wispandono; Kurniawaty Kurniawaty (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Work behavior is an individual response or reaction that arises either in the form of an action or attitude or a person's opinion of his work. This study aims to analyze organizational behavior in the work environment of the Project Management Consultant - Central Sulawesi Rehabilitation and Reconstruction Project (PMC - CSRRP). This study uses a qualitative approach and implements the case study method. Thus, the unit of analysis observed was organizational behavior in the PMC CSRRP environment, with research elements emphasizing three aspects of the discussion of organizational behavior, namely: the study of individual behavior regarding how to understand individual behavior as seen from characteristics, personality, espoused values, perceptions, attitude; then group behavior regarding communication, leadership, and exercised power in the company; and finally the organization, which is seen from the organizational system that is run, and Thompson's propositions that can be applied in organizations. Data collection was carried out using interviews and observation. The results of the study showed that there was differences in work behavior among employees, because each employee had a different personality, basic skills, family background and educational background.